Effect Organizational Culture and Leadership Style on Turnover Intention through Work Motivation as an Intervening Variable - Inayah, Maulidah Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
To empirically demonstrate the effect of organizational culture and leadership style on turnover intention, this study uses work motivation as an intervening variable. Personnel of PNM Mekaar Regional Lamongan were the subjects of the study, which used a quantitative research design. The target population of the study was 630 employees of PNM Mekaar Regional Lamongan, and a sample of 243 employees was obtained by applying the Slovin formula. to the sample calculation. Proportionate random sampling is the method of sampling that will be applied in this study. Surveys are the approach used to collect data. The research sample was given questionnaires to complete as part of the survey. This study used a structural equation model with Smart analytic techniques. PLS 4. The study's findings demonstrate the beneficial and noteworthy effects of The impact of leadership style and corporate culture on workers' motivation at work. The intention to leave an organization is significantly impacted negatively by both organizational culture and leadership style. Workplace motivation significantly and negatively affects turnover intention